Morphological description and statistical characteristic simulation of cocoon filament size curve. Issue 1 (April 2021) - Yang, Pengmin; Ning, Wane; Huang, Jiwei; Ge, Guoping
Abstract: Computer simulation of silk reeling is an important means to understand structure and formation of raw silk, and simulation to generate cocoon filament size curve is the premise of computer simulation of reeling silk. In this paper, according to unique pattern of cocoon filament size curve that is "thin-thick-thin, the last part is the thinnest", a simulation and generation method of cocoon filament size curve with adjustable morphological is obtained by analyzing the characteristic point values and statistical data of cocoon filament size curve, such as head end size, maximum size and its position on cocoon filament, length of cocoon filament. Through a lot of simulation practice and analysis on statistical characteristics of cocoon filament size curve, it is considered that the proposed generation method has good applicability.